Gerakan Literasi untuk Meningkatkan Minat Baca, Tulis dan Hitung Siswa SDN Gongseng Jombang - Rohmat Hidayat; Emi Lilawati; Mochammad Syafiuddin Shobirin; Atiq Masluhah; Nana Russitta; Jamilatun Nazidah; Siti Istinganah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Literacy is an important competency needed by elementary school students to understand and evaluate the information they receive, as well as to express themselves appropriately and effectively. This community service program aims to increase students' interest in reading, writing and arithmetic at SDN Gongseng Jombang. The method used in this program is the Community Education Method in the form of seminars with the aim of equipping strategic audience in increasing interest in reading, writing and arithmetic. The stages carried out in carrying out this program begin with planning, implementing the core activities of the seminar and closing with an evaluation of the implementation of activities. The audience involved in this activity were students of class VI at SDN Gongseng, totaling 38 students. In general, activities can take place very well. This can be seen from the enthusiasm of the audience in attending the seminar and good responses and feedback from the audience. Based on the results of the students' questionnaire, it was obtained: (1) Literacy seminars can foster knowledge and insight into students, (2) Literacy seminars can increase students' interest in reading, writing, and arithmetic, (3) literacy seminars can motivate students to study more actively, (4) Interesting and fun way of delivering material, (5) Reading, writing and arithmetic literacy seminars can trigger the teachers to hold other literacy seminars.